Refractory pollutants removal from industrial wastewater by a coupled process of coagulation-flocculation and alternative electrochemical advanced oxidation processes - Can-Guven, Emine; Bayat, Muhammed Enes; Guvenc, Senem Yazici; Varank, Gamze (ELSEVIER, 2025)
This study aimed to provide discharge standards in the treatment of adhesive production industry wastewater. For this purpose, the coagulation-flocculation process was applied as a pretreatment to remove high suspended solids content and reduce organic load. To select the most effective coagulant, different coagulants were used and the operating parameters of initial pH, oxidant dose, and mixing time were optimized for each coagulant. At the end of the first stage treatment, the optimum process parameters for polyaluminum chloride sulfate (PACS), which was selected as the most effective coagulant, were determined as initial pH 5, coagulant dose 0.5 g/L, and mixing time 15 minutes. In the second stage, alternative electrochemical advanced oxidation processes (AOPs) (electrochemical peroxidation (EP), electro-Fenton (EF), and peroxy-coagulation (PC)) were applied to the coagulation-flocculation effluent, and the most feasible process was selected by evaluating the processes in terms of pollutant removal efficiencies and operating costs. The coagulation effluent concentration of the wastewater with an initial chemical oxygen demand (COD) concentration of 9884 mg/L was reduced to 1532 mg/L, and the final COD concentrations were reduced to 88.9, 544, and 325 mg/L by EP, EF, and PC processes, respectively. Based on the pollutant removal efficiencies and process costs, it was concluded that EP was the most suitable AOP for PACS-coagulated adhesive production industry wastewater.
Keywords: Advanced oxidation; Industrial wastewater treatment; Pre-treatment; Process cost; Sequential treatment; CHLORIDE-SULFATE PACS; ELECTRO-FENTON; LEACHATE TREATMENT; BIODEGRADABILITY; ELECTROOXIDATION; WASTEWATERS; PERFORMANCE; REDUCTION; EFFLUENT; COD; Chemistry